MAKNA BELAJAR ONLINE BAGI MAHASISWA YANG BERPRESTASI DI PRODI PENDIDIKAN SEJARAH UNIVERSITAS 17 AGUSTUS 1945 BANYUWANGI - Widianto, Adita Taufik (Nusantara Hasana Journal, 2022)
This research was conducted to study the outstanding students of the history education study program at the University of 17 August 1945 Banyuwangi. The existence of achievements is important to understand amid changing trends in the learning process during the Covid 19 pandemic. The existence of learning achievements is a sign that there are still students who strive to take actions above the average despite experiencing various difficult situations in the learning process that are different from face-to-face learning at before Covid 19. This study uses a qualitative design through the phenomenological perspective of Alfred Schutz. Schutz's perspective is considered stable enough to be used because it is able to provide an overview of the process of one's actions. The results of this study found that the existence of student achievement is influenced by the deposition of past experiences and motivation to excel.